Pengaruh Perkembangan Teknologi Sebagai Bentuk Perubahan Sosial dalam Pelayanan Data Kependudukan (E-Ktp) di Indonesia Upaya Penerapan Prinsip Good Governance - Anisa Putri Tambun; Novelia Damayanti; Krisna Yuliana Sari; Ivan Darmawan (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
This journal article aims to describe, analyze, and describe the Effect of Science and Technology Development on Population Data Services in Indonesia as an Effort to Apply the Principles of Good Governance. The research method used is a qualitative method. This method looks at natural phenomena through research subjects, such as actions, understandings, foundations/motivations, and others. This approach uses a library study data collection technique or literature study. The results of the research show that the influence of science and technology development on population data services (E-KTP) in Indonesia is generally quite effective because it fulfills several principles of good governance. However, in practice it is faced with various obstacles so that not all principles of good governance can be implemented effectively, especially at the sub-district level of government.